Determinan Keputusan Para Pelaku Usaha Mikro Kecil Dan Menengah (UMKM) Menggunakan Pembiayaan Syariah Di Sumatera Utara - Multamuddin Multamuddin; Saparuddin Siregar; Fauzi Arif Lubis (Owner : Riset dan Jurnal Akuntansi, 2023)
The government, through Bank Indonesia, established the Bank Indonesia National Strategy in developing MSMEs with the aim of realizing MSMEs as a new source of growth for the Indonesian economy through three pillars, namely corporatization, capacity and financing. This study aims to analyze the determinants of decisions of micro, small and medium enterprises that use sharia financing in North Sumatra. The research method uses a quantitative explanatory approach, namely explaining the relationship between influencing variables or causality. The results of the study show that financial attitudes, Islamic financial literacy, Islamic financial inclusion have an effect on the intention to use Islamic financing. And behavioral intentions influence decision making using Islamic financing. And financial attitudes, Islamic financial literacy, Islamic financial inclusion have a direct effect on making financial decisions using Islamic financing. Then indirectly financial attitudes, financial efficacy, Islamic financial literacy, Islamic financial inclusion influence decision making using Islamic financing through the behavioral intentions of MSMEs in North Sumatra. However, the financial efficacy of MSME owners in North Sumatra has no effect on intentions and decision-making using Islamic financing, and does not affect decision-making behavior on the use of Islamic financing through behavioral intentions.